2018
DOI: 10.1016/j.jad.2018.07.069
|View full text |Cite
|
Sign up to set email alerts
|

Problematic eating behaviours, changes in appetite, and weight gain in Major Depressive Disorder: The role of leptin

Abstract: The results provide new information about associations between leptin, sex-specific weight and appetite changes and problematic eating behaviours, which may be risk factors for cardiovascular and metabolic diseases in MDD, particularly in females. Future longitudinal research investigating leptin as a risk factor for weight gain in MDD is warranted, and may lead to early interventions aimed at preventing weight gain in at-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 76 publications
5
31
1
Order By: Relevance
“…A recently published study analysing plasma levels of leptin in young adults revealed a positive association between plasma leptin levels and selfreported depressive symptoms, especially for women [57]. Indeed, several previous studies displayed a clear sex difference of leptin levels, with females having higher amount than males [57][58][59]. Carvalho et al in their meta-analytic study published in 2014, found higher peripheral leptin levels in participants with mild to moderate major depressive disorder compared with controls, but no significant difference between controls and severely depressed patients [60].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 97%
“…A recently published study analysing plasma levels of leptin in young adults revealed a positive association between plasma leptin levels and selfreported depressive symptoms, especially for women [57]. Indeed, several previous studies displayed a clear sex difference of leptin levels, with females having higher amount than males [57][58][59]. Carvalho et al in their meta-analytic study published in 2014, found higher peripheral leptin levels in participants with mild to moderate major depressive disorder compared with controls, but no significant difference between controls and severely depressed patients [60].…”
Section: Leptin and Psychiatric Illnessesmentioning
confidence: 97%
“…In a recent pilot, we found that 25% of a sample with MDD met Yale criteria for food addiction, considerably higher than general community samples (Mills et al, 2018).…”
Section: Introductionmentioning
confidence: 86%
“…Several studies have linked the concept of food addiction to MDD (e.g. Gearhardt et al, 2012;Eichen et al, 2013;Mills et al, 2018). As such, it is possible that obesogenic environments promoting the availability of highly palatable foods may be related to the increased prevalence of atypical MDD characterised by weight gain, however further research is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations